Food insecurity and vitamin D deficiency factors, and effects of vitamin D supplementation on metabolic syndrome among food insecure and vitamin D deficient Iranian elderly - Zarei, Maryam (2019)
In almost every country, elderly population is growing faster than any other age groups with its age-related lifestyle changes, physical disabilities potentially chronic disease ultimately forcing them to remain indoors. The above factors may directly affect their ability to have access to food as well as potentially being impacted by food insecurity. Food insecurity can contribute to poor health and nutrition deficiency of which vitamin D deficiency is the most common one seen in older adults. Although there are numerous studies have been conducted on the effects of vitamin D supplementation in adults, but little or no data has been reported on the effects of vitamin D supplementation in older adults with vitamin D deficiency, especially amongst Iranian older adults. This study comprised of two phases; the first phase was a cross-sectional, conducted to determine the prevalence and factors associated with food insecurity and vitamin D deficiency among older adults in Karaj city, Iran. Study subjects were recruited based on a defined set of inclusion criteria via systematic random sampling. An interviewer-administered questionnaire was used to capture information on socioeconomic characteristics, medical history, and food security status, sun exposure and food frequency questionnaire (FFQ). Anthropometric measurements including weight, height and waist circumference as well as blood pressure were measured by trained research staff directly after the interview. Fasting blood samples were collected for quantifying serum 25-hydroxyvitamin D [25(OH) D] level. Adjusted logistic regression was used to identify associations between food insecurity, vitamin D deficiency and selected predictor variables. The second phase of this study was a randomized control trial (RCT) to examine the effects of vitamin D supplementation on metabolic syndrome parameters such as [body mass index (BMI), waist circumference (WC), blood pressure (BP), total cholesterol (TC), triglyceride (TG), low-density lipoprotein (LDL-C), high-density lipoprotein (HDL-C), fasting blood sugar (FBS)], and as well as 25(OH)D concentration among food insecure and vitamin D deficient older adults, before and after 2 months supplementation with vitamin D in Karaj city, Iran. Out of 422 subjects from phase I, a total of 120 food insecure subjects were enrolled into phase 2 of the study. Food insecure subjects were vitamin D deficient (< 30 ng/ml), and with at least one metabolic syndrome parameters (from self-reported medical history) were included to phase two via simple allocation randomisation. The subjects (60 intervention and 60 placebo) were assigned to receive either weekly vitamin D supplement (intervention group: 50,000 IU 25(OH) D3) or a placebo capsule (placebo group) for two months. Fasting blood samples were collected for quantifying serum 25(OH) D level, FBS and lipid profile at baseline and after completing two months treatment. Anthropometric characteristics, blood pressure (BP) and blood collection were monitored by using analysis of covariance at baseline and after intervention. Result from phase one showed that 31.7% older adults were food insecure while 60.4% were vitamin D deficient with a higher rate among the females. Logistic regression analysis indicated that a minimum household income of 800,000 T (160 $USD), and having more than three metabolic syndrome parameters significantly increased the odds of food insecurity by almost 16-fold (AOR = 16.27, 95% CI = 8.09 - 30.28) and 5-fold (AOR = 4.615, 95% CI = 2.654 - 8.877), respectively. Obese respondents had significantly higher odds (AOR = 3.105, 95% CI = 1.933 - 4.987) of food insecurity by almost three-fold. Food insecure older adults were more likely to consume high energy (AOR = 1.477, 95% CI = 1.139 - 1.944), and carbohydrate (AOR = 1.710, 95% CI = 1.112 - 2.631) intakes compared to food secure older adults. Food insecure older adults were also more likely to be vitamin D deficient (AOR = 1.472, 95% CI = 0.953 - 2.273). In addition, being a female increased odds of vitamin D deficiency by two-fold (AOR = 1.810; 95% CI = 1.181- 2.772), whilst obesity increased odds of vitamin D deficiency by almost five-fold (AOR = 4.703; 95% CI = 2.312 - 9.566). In phase two of the study, supplementation of vitamin D3 for two months improved mean change of FBS, TG, TC, LDL-C and systolic BP (p = 0.004, p = 0.001, p = 0.001, p = 0.003, p = 0.001, respectively), and resulted in a significant improvement of mean serum 25(OH) D concentration in the intervention group compared to the control group (p = 0.001). No significant differences were observed when comparing body weight status, WC, diastolic BP and HDL-C between intervention and control groups at baseline and after intervention. In summary, this study indicated that a significant level of food insecurity is present in older adults in Iran which was associated with socioeconomic factors, dwelling arrangements. This in turn affected prevalence of chronic diseases such as vitamin D deficiencies and decreased health-related quality of life in older adults. Vitamin D deficiency had detrimental effects on health in older adults while vitamin D supplementation improves vitamin D status and a number of risk factors for cardiovascular disease. Therefore, replenishing vitamin D levels in older adults could reduce premature morbidity and mortality in food insecure older adults.